Zagrożenie terroryzmem a bezpieczeństwo przemysłu chemicznego w Polsce na przykładzie zakładów chemicznych PCC Rokita SA - Grobelny, Piotr; Malarz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article discusses the problem of the security of the chemical industry in Poland as exemplified by the chemical company PCC Rokita SA in the context of terrorist threats. Terrorist threats concern all buildings and facilities: public, private, business-related, especially critical infrastructure facilities, including chemical plants. In the case of chemical plants terrorist threats are twofold. Firstly, terrorists may become interested in attacking a chemical plant owing to the fact that the warehouse of such a plant contains substances, products and components used by terrorists to produce their weapons. Secondly, terrorists may become interested in attacking a chemical plant owing to the fact that chemical plants are part of the critical infrastructure.
Keywords: PCC Rokita S.A.; threats to company security; terrorism; security threats